Here be dragons! Reconciling Indigenous and Western knowledge to improve Aboriginal child welfare - LaFrance, Jean; Bastien, Betty (First Peoples Child & Family Review, 2007)
The authors discuss the factors regarding the reconciliation movement in reconciling Indigenous and Western Knowledge to improve child welfare practice with respect to Aboriginal peoples. In particular, a current initiative undertaken in collaboration with various First Nation communities in Alberta involved with the “Making Our Hearts Sing” Initiative is highlighted. This initiative aimed to build on collaboration among child welfare stakeholders and Aboriginal communities to examine issues relating to child welfare that would be more in keeping with traditional Aboriginal worldviews that could, at the same time, contribute to reconciliation, healing and increased community capacity.